2018
DOI: 10.1161/jaha.118.009545
|View full text |Cite
|
Sign up to set email alerts
|

Variants at the APOE/C1/C2/C4 Locus Modulate Cholesterol Efflux Capacity Independently of High‐Density Lipoprotein Cholesterol

Abstract: BackgroundMacrophage cholesterol efflux to high‐density lipoproteins (HDLs) is the first step of reverse cholesterol transport. The cholesterol efflux capacity (CEC) of HDL particles is a protective risk factor for coronary artery disease independent of HDL cholesterol levels. Using a genome‐wide association study approach, we aimed to identify pathways that regulate CEC in humans.Methods and ResultsWe measured CEC in 5293 French Canadians. We tested the genetic association between 4 CEC measures and genotypes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
33
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 41 publications
5
33
1
1
Order By: Relevance
“…Also in line with these and our findings, a recent genomewide association study found CEC apoB-free plasma associated with variants in genes encoding proteins involved in the formation and metabolism of HDL rather than for minor and nonclassical protein components of HDL (40). Beyond classical genes of HDL metabolism such as the APOLP1 and APOLP2 loci, CETP, LIPC, or LPL, 2 loci including the PLB1 and ENPP7 genes -which encode for enzymes degrading phosphatidylcholines and sphingomyelins -were the only ones associated with CEC apoB-free plasma (40). Thus, general physicochemical properties such as number, size, and fluidity of particles rather than specific components appear to determine CEC HDL .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Also in line with these and our findings, a recent genomewide association study found CEC apoB-free plasma associated with variants in genes encoding proteins involved in the formation and metabolism of HDL rather than for minor and nonclassical protein components of HDL (40). Beyond classical genes of HDL metabolism such as the APOLP1 and APOLP2 loci, CETP, LIPC, or LPL, 2 loci including the PLB1 and ENPP7 genes -which encode for enzymes degrading phosphatidylcholines and sphingomyelins -were the only ones associated with CEC apoB-free plasma (40). Thus, general physicochemical properties such as number, size, and fluidity of particles rather than specific components appear to determine CEC HDL .…”
Section: Discussionsupporting
confidence: 92%
“…Likewise, Lusis and colleagues found apoA-I and medium-sized HDL, rather than any minor HDL proteins, to be the most important explanatory factors of differences in CEC HDL from different mouse strains (39). Also in line with these and our findings, a recent genomewide association study found CEC apoB-free plasma associated with variants in genes encoding proteins involved in the formation and metabolism of HDL rather than for minor and nonclassical protein components of HDL (40). Beyond classical genes of HDL metabolism such as the APOLP1 and APOLP2 loci, CETP, LIPC, or LPL, 2 loci including the PLB1 and ENPP7 genes -which encode for enzymes degrading phosphatidylcholines and sphingomyelins -were the only ones associated with CEC apoB-free plasma (40).…”
Section: Discussionsupporting
confidence: 89%
“…recessive Tangier disease, LCAT deficiency or apo A-I deficiency) [57]. As with severe hypertriglyceridemia, polygenic factors like heterozygous rare variants with incomplete penetrance and extreme polygenic SNP scores, were much more common among individuals with very low HDL cholesterol [56]. Also, we detected heterozygous large-scale deletions of ABCA1 in four patients with severely lowered HDL cholesterol, the first report of ABCA1 CNVs in the context of this phenotype [39].…”
Section: Discussionmentioning
confidence: 66%
“…We report our clinical and research experience with LipidSeq, a targeted hybrid panel designed for clinical resequencing of genomic loci known to be associated with dyslipidemia and related metabolic traits and disorders. Since 2014, the results from this panel have contributed to 39 publications reporting original scientific findings, including seven on FH [32,43,44,[46][47][48][49], seven on hypertriglyceridemia [42,45,[50][51][52][53][54], four on extremes of HDL cholesterol [39,[55][56][57], and 21 case reports [40,41,[58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74][75][76]. We have published an additional 15 reviews and methods articles related to this work [4, 5, 7, 11-13, 20, 34, 77-83].…”
Section: Discussionmentioning
confidence: 99%
“…For example, APOE, which has been associated with modulation of total cholesterol 34 [28][29][30][31] supporting their links with cholesterol. b) ACSM5 pairs as an eGene with rs11647589, rs6497490, and rs1394678, which were associated with 3-phenylpropionate, X-11478 (an unknown metabolite), and indolepropionate respectively.…”
Section: Metabolite-associated Snps Mark Eqtlsmentioning
confidence: 92%